Local Hemostatic Activity of Psidium guajava Leaves in Swiss Webster Mice - Cszahreyloren Vitamia; Angga Saputra (Universitas Padjadjaran, 2017)
Psidium guajava (P. guajava) leaves have been empirically used to stop bleeding. Tannin, one of this plant's secondary metabolites, may contribute to this activity. However, information regarding its pharmacologicy activity was limited. Therefore, this study was performed to evaluate local hemostatic activity of P. guajava leaves. This study used Duke method with male Swiss Webster mice as test animals. The animals were grouped into three i.e., negative control (distilled water), positive control (epinephrin), and P. guajava group. Its tail was cut (2-3 mm) and the bleeding time was calculated. Statistical analysis was performed using Kruskal-Wallis test and continued with Least Significant Different (LSD) test. The mean (SD) of bleeding time for those groups were 246.00 (22.95), 72.40 (5.55), and 88.40 (7.03), respectively. There was a significant difference between the negative control group with the other two groups, but there was not significant difference between the positive control group and the P. guajava group. In conclusion, P. guajava showed promising local hemostatic activity and can be further developed as potential hemostatic agents. Keywords: Psidium guajava, hemostatic, bleeding time